Insurance status as a mediator of clinical presentation, type of intervention, and short-term outcomes for patients with metastatic spine disease. (February 2022) - Price, Meghan J.; De la Garza Ramos, Rafael; Dalton, Tara; McCray, Edwin; Pennington, Zach; Erickson, Melissa; Walsh, Kyle M.; Yassari, Reza; Sciubba, Daniel M.; Goodwin, Andrea N.; Goodwin, C. Rory
Abstract: Background: It is well established that insurance status is a mediator of disease management, treatment course, and clinical outcomes in cancer patients. Our study assessed differences in clinical presentation, treatment course, mortality rates, and in-hospital complications for patients admitted to the hospital with late-stage cancer – specifically, metastatic spine disease (MSD), by insurance status. Methods: The United States National Inpatient Sample (NIS) database (2012–2014) was queried to identify patients with visceral metastases, metastatic spinal cord compression (MSCC) or pathological fracture of the spine in the setting of cancer. Clinical presentation, type of intervention, mortality rates, and in-hospital complications were compared amongst patients by insurance coverage (Medicare, Medicaid, commercial or unknown). Multivariable logistical regression and age sensitivity analyses were performed. Results: A total of 48, 560 MSD patients were identified. Patients with Medicaid coverage presented with significantly higher rates of MSCC (p < 0.001), paralysis (0.008), and visceral metastases (p < 0.001). Patients with commercial insurance were more likely to receive surgical intervention (OR 1.43; p < 0.001). Patients with Medicaid < 65 had higher rates of prolonged length of stay (PLOS) (OR 1.26; 95% CI, 1.01–1.55; p = 0.040) while both Medicare and Medicaid patients < 65 were more likely to have non-routine discharges. In-hospital mortality rates were significantly higher for patients with Medicaid (OR 2.66; 95% CI 1.20–5.89; p = 0.016) and commercial insurance (OR 1.58; 95% CI 1.09–2.27;p = 0.013) older than 65. Conclusion: Given the differing severity in MSD presentation, mortality rates, and rates of PLOS by insurance status, our results identify disparities based on insurance coverage. Highlights: Patients with MSD who have Medicaid are more likely to present with later stage disease and more severe symptom burden. Patients with MSD and private insurance are more likely to receive surgery than those with government insurance. Rates of in-hospital mortality, non-routine discharge, and PLOS differ by the insurance status and age of patients with MSD.